Effectiveness of Integrated Cognitive-Behavioral and Emotion-Focused Therapy on Psychological Hardiness, Financial Stress Tolerance, and Family Resilience in Conflicted Couples - Zargari, Parmis; Ghasemi, Mahsa; Esmaeilpour, Mozhgan; Adhami Vishkaee, Somayeh (Mental Health and Lifestyle Journal, 2024)
The present study aimed to examine the effectiveness of integrated cognitive-behavioral and emotion-focused therapy on psychological hardiness, financial stress tolerance, and family resilience in conflicted couples. This study employed a quasi-experimental design with a pretest–posttest and follow-up structure, including an experimental group and a control group. The statistical population consisted of conflicted couples referring to counseling centers in Tehran, from which 60 couples (120 individuals) were selected through purposive sampling and randomly assigned to experimental and control groups (30 couples each). The experimental group participated in twelve 90-minute sessions of integrated cognitive-behavioral and emotion-focused therapy, while the control group received no intervention. Data were collected at three stages: pretest, posttest, and two-month follow-up. Measurement instruments included the Personal Views Survey for psychological hardiness, the Financial Anxiety Scale for financial stress tolerance, and the Family Resilience Assessment Scale. Data analysis was conducted using repeated measures analysis of variance (ANOVA) and Bonferroni post-hoc tests in SPSS-27 at a significance level of 0.05. The results of repeated measures ANOVA indicated significant main effects of time and group, as well as significant interaction effects of time × group for psychological hardiness, financial stress tolerance, and family resilience (p < 0.001). The effect sizes for the interaction effects were large, indicating a substantial impact of the intervention on all dependent variables. Bonferroni post-hoc comparisons revealed significant differences between pretest and posttest, as well as pretest and follow-up stages (p < 0.001), while no significant differences were observed between posttest and follow-up, suggesting the stability of treatment effects over time. The findings demonstrate that integrated cognitive-behavioral and emotion-focused therapy is an effective and sustainable intervention for enhancing psychological hardiness, improving tolerance to financial stress, and strengthening family resilience in conflicted couples, highlighting the value of combining cognitive and emotional approaches in couple therapy.